PROBLEMS IN INTERPRETING COLLOCATIONS FROM MACEDONIAN INTO ENGLISH AND VICE VERSA (Journal of Contemporary Philology, 2022)
This paper talks about language propensity to transfer information and connect it to the act of interpreting, explaining what interpreting is and distinguishing between consecutive and simultaneous interpreting. It goes on to introduce the concept of collocations by defining and classifying them, and providing examples for each type so as to make the distinction clearer. It connects proper use of collocations and better language user competence, imperative for interpreters. Then it presents and covers an original research conducted with university students of consecutive and simultaneous interpreting from Macedonian into English language and vice versa analysing the students’ knowledge and proper use of collocations connected to two specific topics – economy and politics. It also exemplifies the different types of mistakes the students made in their renditions and analyses the sample of collocations, specifically observing the most and least common types of collocation structures present in the sample of examples. Finally, the paper concludes that around 50% of the analysed collocations are incorrectly rendered by the students, which stresses the importance of introducing collocations in the curricula of interpreting, therefore language learning as well.
Keywords: collocations; language learning; research; mistakes; interpretation